Efflux Pump Inhibitory Potential of Vitexin 2"-O-xyloside Against Gram Positive Bacteria Staphylococcus aureus - Munira, Sirazum; Zaman, Shadid Uz; Muhit, Md Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Expression of bacterial efflux pump is one of the major causes for developing antibiotic resistance in a variety of pathogens. Efflux pump inhibitors (EPIs) are potential molecules that can antagonize those pumps and help in alleviating the resistance problem. The study was aimed to explore the EPI activity of vitexin 2"-O-xyloside, an apigenin flavone glycoside. A total 15 clinical isolates of Staphylococcus aureus were collected and their antibiotic resistance profiles were detected by Kirby-Bauer disc diffusion assay and MIC values were determined through broth microdilution technique. Prevalence of efflux pump activity were examined through ethidium bromide agar-cartwheel method. Fractional inhibitory assay was carried out in combination with tetracycline and ciprofloxacin against clinical isolates of S. aureus with efflux pump activity. Finally, molecular docking approach was carried out in the active binding sites of NorA efflux pump protein by Autodock Vina. All of the clinical isolates showed resistance to cefixime, ciprofloxacin and tetracycline antibiotics whereas all of them were sensitive to chloramphenicol. Efflux pump was found active among 20% of the clinical isolates. The tested compound showed additive effective (ƩFIC value 0.625 – 0.75) when co-treated with tetracycline in the efflux pump active isolates which was similar to reserpine. Molecular docking studies showed that vitexin 2"-O-xyloside may bind to the different binding sites, opening the door for it to be considered as a potential EPI. Dhaka Univ. J. Pharm. Sci. 20(3): 307-315, 2022 (June) Centennial Special Issue